Faith in the family : a lived religious history of English Catholicism, 1945-82 - Harris, Alana, 1973- (Manchester : Manchester University Press, 2013)
Drawing upon a multi-disciplinary methodology employing diverse written sources, material practices and vivid life histories, 'Faith in the Family' seeks to assess the impact of the Second Vatican Council on the ordinary believer, alongside contemporaneous shifts in British society relating to social mobility, the sixties, sexual morality and secularisation.
Includes bibliographical references and index.
Description based on print version record.
Master record variable field(s) change: 072
Keywords: Catholic Church -- England -- History -- 20th century; Catholic Church; Catholics -- England -- Social conditions -- 20th century; Catholics -- England -- History -- 20th century; RELIGION -- Christian Church -- History; Catholics; Catholics -- Social conditions; Influence (Literary, artistic, etc.); England; 1900-1999; Electronic books; History